THE HERSEY-BLANCHARD SITUATIONAL LEADERSHIP MODEL IN ENHANCING EMPLOYEE PERFORMANCE AT THE CLASS IIA WOMEN'S CORRECTIONAL INSTITUTION IN BANDUNG - Adani, Firnas; Nurhadi, Sheravina; Priyatmono, Budi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Correctional Institutions (Lapas) encounter several challenges related to organizational complexity, such as high population density, limited human resources, and significant work pressure, all of which impact employee performance. In this context, the application of the Hersey-Blanchard situational leadership model is an important strategy to improve the effectiveness and efficiency of services at the Class IIA Bandung Women's Prison. This study uses a qualitative descriptive approach that aims to analyze adaptive role leadership in managing diverse employees and adjusting leadership styles according to their level of readiness and competence. The results of the study indicate that situational leadership style is able to strengthen work motivation, improve communication, and improve employee performance through an appropriate adjustment approach according to the situation at hand. This model is expected to provide a positive contribution in creating a more productive, adaptive work environment that is able to face organizational challenges effectively. Keywords: Leadership; Employee Performance; Correctional Institutions